Faktor-Faktor yang Memengaruhi Tingkat Pendapatan Petani Karet di Desa Sako Suban, Kecamatan Batang Hari Leko, Sumatera Selatan - Iman Satra Nugraha; Aprizal Alamsyah (Institut Pertanian Bogor, 2019)
Revenue is an important thing for farmers, because with the income the farmers can meet the needs of the household. The higher the income then the welfare of farmers will be improved. The purpose of this research is to identify the characteristics of farmers, analyze farmers' income and factors affecting the income level of rubber farmers in Sako Suban Village. The selection of villages was done purposively but the selection of respondents was conducted by accidental sampling. The data used in the primary data were collected by using interview method. Quantitative data processing used linear regression by using a significant level of 10%. The results of the research showed that the education of the farmers was low, the average age of the farmers was 46 years, and the majority of the farmers work as rubber farmers. Rubber contributed 63% to the total revenue and the rest comes from company laborers and loggers and average farmer incomes was IDR733.389/month. Variables that affect farmers' income are rubber prices, farmers groups, and farmers experience in rubber gardening. The variables that have no significant effect on farmers' income are the education of farmers, the labor in the family, and the land area.